Molecular phylogeny and morphology reveal a new wood-inhabiting fungus, Hyphoderma cinereofuscum (Polyporales, Basidiomycota), from southwest China - Li, Wen; Wang, Xiyan; Chen, Daxiang; Zhang, Sicheng; Li, Yunchao; Zhao, Changlin; Zhan, Zhongyi (Phytotaxa, 2025)
Hyphoderma is one of the important representative groups of wood-inhabiting fungi. These fungi secrete various enzymes capable of degrading cellulose, hemicellulose, and lignin into simple inorganic substances. The taxa within the genus cause a white rot of wood, play a key role in the carbon cycle and are the most efficient wood decomposers in the forest ecosystem. This study proposes a new wood-inhabiting fungal taxon, Hyphoderma cinereofuscum, based on morphological features and molecular evidence. It is characterized by the white hymenial surface, a monomitic hyphal system, generative hyphae with simple-septa, colorless, thin-walled, the presence of the tubular and capitate cystidia, and cylindrical basidiospores 9–11.5 × 4.5–5 µm. The phylogenetic tree inferred from a combination of the internal transcribed spacer regions (ITS) and the large subunit nuclear ribosomal RNA gene (nLSU) revealed that Hyphoderma cinereofuscum nested in the Hyphoderma clade and is closely related to H. marginatum. A full description, illustrations and phylogenetic analysis results of the new species are provided.